The use of technological and communication media to document socioemotional education experiences in a Danish school (Innovaciones Educativas, 2021)
The changes inherent to the globalization process of the 21st century have required a series of modifications in the educational environment. The scenario of mass and communication technologies motivates one to create a documentation of educational practices. In a framework of socio-emotional education for the development of emotional competencies in children, having a memory of the methodologies developed is of fundamental importance. The following study analyzes the documentation process during a stay in a Copenhagen school. The participants are the teachers and students of a school located in the district of Nørrebro, in the city of Copenhagen, selected to analyze how their teaching style includes emotional education objectives. The variables measured refer to the use of technological and communication means to support the practice of observation and documentation, in a qualitative research approach. The documents created through the technological and communication media chosen to document the practices are presented. In addition, the information collected from projects that lead students to promote personal well-being is offered. Finally, the innovative aspects of the practices developed in the school and, also, the beneficial contributions of the different technological means are highlighted. In particular, the effectiveness of a dissemination of experiences through the support of social networks and implementation of a training process on socio-emotional education for teachers is highlighted. In the future, the extension of these documentation processes in educational centers of different cultural contexts is planned.
Keywords: Basic education; knowledge dissemination; observation; teaching; social networks; socio-emotional skills